Szegénylegények . The Round-up - Jancsó, Miklós (MAFILM, 1965)
Duration: 01:35:00 With the Austrian hegemony re-established in Hungary after the crushing of the 1848 revolution, in 1869 count Gedeon Ráday government commissioner is charged with the task of improving public safety in the country. He focuses on rounding up the poor and the outlaws who fought on the side of Sándor Rózsa in the revolution and jails them in an isolated fort in the Great Plain. The authorities do not know who the revolutionary leaders are but they are suspected to be among the prisoners and the investigation begins.